Performance of Local Versus International Focus Malaysian- Based Mutual Funds - Ruzita Abdul Rahim; Ling Pick Soon; Rasidah Mohd Rashid (Asian Academy of Management Journal of Accounting and Finance, 2019)
In light of the liberalisation in Malaysia’s mutual fund industry, this study examines the performance of 180 internationally-focused against 191 locally-focused Malaysian-based funds using augmented Henriksson-Merton market timing model on daily data starting from January 1995 until December 2015. The results show that the funds generally outperform the market, despite the persistently perverse market timing ability. Although geographically disadvantaged, locally-focused funds prove to be superior to the internationally-focused funds both in terms of returns and risks owing to the informational advantage to better select the stocks from their own market. The results also reveal that size effect is imminent regardless of geographical focus, value investing is significant only among locally-focused funds, while momentum is marginally effective.